Potensi Sektor Perekonomian di Kabupaten Malinau Provinsi Kalimantan Utara - Dio Caisar Darma; Haryadi Haryadi; Etik Umiyati (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2015)
This study uses LQ Analysis Tool, DLQ, Shift Share, and Overlay during 5 yeares (2009 – 2013). As for the operating variable in this study is the GDP at Constant Prices, Economic Growth, Growth Sector, in the economy of Malinau Regency and the North of Borneo Province. Based on the results of the analysis are sector LQ base (seed) in Malinau Regency is agriculture, electricity, gas and water, building and construction sector, the hotel and restaurant trade, and services sectors. DLQ analysis results show that, of the nine in the field of business, only the mining and quarrying sector that has a great chance to be developed in the future. Then, with a Shift Share Analysis results it is known that there is a change in the sectoral aggregate workmanship compared to the changes in the same sector in the economy with the Malinau Regency Regional Share (Rj) of -557,195.12 million rupiah. Shift Differential category (Dj) are seven sector experienced more rapid economic growth in Malinau Regency than North of Borneo Province or Pj <0. From category Proportional Shift (Pj) are eight sectors experiencing economic growth more quickly in Malinau Regency than North of Borneo Province or Pj> 0. The other side, from the results of the Analysis of Overlay, there are six sector, which has a value notation is quite positive and dominant namely: agriculture, electricity, gas and water, building and construction sector, trade, hotels and restaurants, as well as services sector dominates with results notation (+ - +).